Pengaruh Likuiditas, Profitabilitas dan Devidend Payout Ratio terhadap Harga Saham pada Perusahaan Makanan dan Minuman di Bursa Efek Indonesia Periode 2015-2018 - Aprilia Wimas Indrayani; Anita Wijayanti; Yuli Chomsatu Samrotun (Universitas Batanghari Jambi, 2020)
Stock price is one important indicator in a company, this shows how much interest investors to invest in a company. The stock price is also an indicator of the success of management in managing the company. the purpose of this study was to analyze the effect of CR, ROA, NPM, and DPR on stock prices. This research includes quantitative research by referring to the analysis of company performance which is used as a reference to predict future stock prices. This research was conducted at food and beverage companies listed on the Indonesia Stock Exchange (IDX) in the 2015-2018 period. The sampling method used in this study is based on a purposive sampling technique that is in accordance with the criteria of 11 food and beverage companies used in this study collected through the observation method using data registered on the IDX. Testing of hypotheses in this study uses multiple linear regression analysis that is sampled. The results of the research show that there is an influence of CR, ROA, NPM, and DPR on the 2015-2018 price of food and beverage company stock. The benefits of this research are as a material for consideration in making decisions regarding CR, ROA, NPM and DPR on share prices and as a reference to improve company performance in achieving the goals set by the company.